Pemetaan Ruang Terbuka Hijau di Kecamatan Limboto Kabupaten Gorontalo - Bina, Fadlyanto; Yusuf, Daud; Pratama, M. Iqbal Liayong (Universitas Negeri Gorontalo, 2026)
Green Open Space (GOS) plays an important role in maintaining environmental balance in urban areas. However, rapid development and land-use changes have caused a decrease in the availability of Green Open Space in Limboto District, Gorontalo Regency. This study aims to map the distribution of public Green Open Space and analyze its availability based on the area in Limboto District, Gorontalo Regency. The research used a descriptive quantitative method with spatial analysis. The data used include administrative boundary data, public Green Open Space distribution data obtained from related institutions, and field survey results. The results show that public Green Open Space in Limboto District is unevenly distributed and only found in several villages. The types of Green Open Space identified include city parks, recreational parks, grand forest parks, urban forests, green corridors, and water body buffer zones. The total area of public Green Open Space is 90.02 hectares or approximately 1.10% of the total area, which does not meet the minimum requirement of 20% public Green Open Space.